Short-term forecasting for direct normal irradiance with numerical weather prediction models in Alentejo (Southern Portugal): implications for concentration solar energy technologies - Lopes, Francisco Manuel Tavares (2021)
With the potential to sustain the world’s energy needs, solar energy plays a major role for the renewable energy transition. However, inherent problems exist in solar energy forecasting, a very important tool for power plant operators that allows an efficient energy management and dispatch operations in the electric grid. In particular, concentrating solar power (CSP) systems, which rely on direct normal irradiance (DNI) and its high variability, which links uncertainty to the electrical energy outputs of CSP plants. The main atmospheric factors that influence DNI variation at surface are clouds and aerosols, which are misrepresented by current numerical weather prediction models. To provide accurate predictions of DNI for efficient CSP operations, particularly during periods of direct solar intermittency, the solar resource needs to be well characterized. Solution to this problem is still one of today’s challenges in solar forecasting. This thesis makes use of short-term forecasts of DNI from the Integrated Forecasting System (IFS), the global model of the European Centre for Medium-Range Weather Forecasts (ECMWF), together with ground-based measurements in Alentejo region (southern Portugal). The evaluation of the solar resource in the region is based on the IFS predictions, as well as the prediction of energy production outputs from different CSP systems through the System Advisor Model (SAM) power plant simulator, in which the results are compared with local measured data. To improve the role that DNI forecasting has in CSP power plants, several post-processing techniques are used for the correction of hour and day-ahead values of DNI. Different operational strategies are discussed and proposed according to the obtained results; Resumo: Previsão de Curto Tempo de Radiação Normal Directa Através de Modelos Numéricos de Previsão do Tempo no Alentejo (Sul de Portugal): Implicações para as Tecnologias de Concentração Solar Com potencial para assegurar as necessidades energéticas do mundo, a energia solar desempenha um papel importante na transição energética renovável. Contudo, existem problemas inerentes na previsão de energia solar, uma ferramenta muito importante para os operadores de centrais eléctricas que permite uma gestão energética mais eficiente e operações de distribuição da mesma na rede eléctrica. Em particular, os sistemas de concentração de energia solar (CSP), que dependem da radiação normal directa (DNI) e da sua elevada variabilidade, atribuindo incerteza à geração de energia eléctrica resultantes de centrais CSP. Para fornecer previsões precisas para operações CSP eficientes, particularmente durante períodos de intermitência solar directa, o DNI precisa de ser bem caracterizado. Os principais factores atmosféricos que influenciam a variação de DNI à superfície são as nuvens e os aerossóis, que não são representados realisticamente pelos actuais modelos numéricos de previsão do tempo. A solução para este problema é ainda hoje em dia um desafio em previsão solar. Esta tese faz uso das previsões de curto-período de DNI do Integrated Forecasting System (IFS), modelo global do European Centre for Medium-Range Weather Forecasts (ECMWF), em conjunto com medidas à superfície na região do Alentejo (sul de Portugal). A avaliação do recurso solar na região é efectuada com base em previsões do IFS, tal como a previsão de outputs de produção energética de diferentes sistemas CSP através do simulador de centrais eléctricas System Advisor Model (SAM), onde os resultados são comparados com os obtidos com medidas meteorológicas locais. Para melhorar o papel que a previsão de DNI tem em centrais CSP, várias técnicas de pós-processamento são efectuadas para a correção de valores de DNI para a hora e dia seguinte. Diferentes estratégias de operação são discutidas e propostas de acordo com resultados obtidos.